The study of the effects of bullet material hardness on the penetration capability of a 7.62x39 mm armor-piercing ammunition by numerical simulation method - Nguyễn Đình, Hùng; Trần Văn, Doanh; Đỗ Văn, Minh; Mai Quốc, Vương; Bùi Xuân Sơn; Đặng Bá, Ngọc (Journal of Military Science and Technology, 2023)
This paper presents the results of research on the effect of the bullet material hardness on the penetration capability of a 7.62 x 39 mm two-component K56-type Armor-Piercing ammunition; establishes the rule of the influence of the bullet material hardness on the residual velocity of the bullet after the steel plate and compares the simulation results with the experiment results of 02 samples of real ammunition at the firing range, compare the residual velocity of the bullet after the steel plate between theory and experiment. The research results contribute to the scientific theoretical basis for calculating, designing, and manufacturing 7.62x39 mm Armor-Piercing ammunition with a two-component structure.